2021
DOI: 10.3390/polym13060861
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist Concepts of Polypyrrole Actuators: Bending Hybrid Actuator and Mirrored Trilayer Linear Actuator

Abstract: Following the natural muscle antagonist actuation principle, different adaptations for “artificial muscles” are introduced in this work. Polypyrrole (PPy) films of different polymerization techniques (potentiostatic and galvanostatic) were analyzed and their established responses were combined in several ways, resulting in beneficial actuation modes. A consecutive “one-pot” electrosynthesis of two layers with the different deposition regimes resulted in an all-PPy bending hybrid actuator. While in most cases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The general trend in current research is to focus on applications, while mechanistic studies are not followed up. To control actuators, the mixed-ion actuation appeared in several studies to lower the overall strain outcome [15], or if in the same size at oxidation/reduction, special design can present new application [30]. Previous research [31] revealed that the typical cation-driven actuators PPy/DBS changed to mainly anion-driven in organic electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…The general trend in current research is to focus on applications, while mechanistic studies are not followed up. To control actuators, the mixed-ion actuation appeared in several studies to lower the overall strain outcome [15], or if in the same size at oxidation/reduction, special design can present new application [30]. Previous research [31] revealed that the typical cation-driven actuators PPy/DBS changed to mainly anion-driven in organic electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Linear strain of the five-layer i EAP actuator at ±1, ±2, and ±3 V. (B) Linear force of single actuator and cumulative force for four stacked actuators at ±3 V. (C) Linear strain–voltage dependency plot of the five-layer i EAP actuator, compared with that of other linear actuators reported in the literature to highlight the impact of low-voltage practical operability of our actuator: CP1, CP2, CP3, CP4, CP5, and CP6 . The strain values at the indicated frequencies are plotted.…”
Section: Resultsmentioning
confidence: 99%
“…Figure C shows a comparison of the linear strain–voltage dependencies of soft actuators reported in the literature over the past 15 years. ,, In the case of trilayer actuators with one ionic membrane between two symmetric electrodes, the typical ion concentration gradient under bias causes an opposite volume change for each electrode, impeding linear deformation . If linear motion is needed, the actuators must be immersed in an electrolyte solution to provide symmetric expansion and contraction force for the outer electrodes via the volume change during a redox reaction, limiting their practical applicability . The only existing ionic actuators capable of low-voltage stimulated linear motion with a strain of over 1% are conducting polymer (CP) actuators. , However, their performance is limited only to wet or submerged conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, by either selecting different electrolytes or solvents or choosing the right polymerization potential, one can promote the desired control of actuation by avoiding mixed modes. On the other hand, mixed actuation with virtually equal strain upon oxidation and reduction allows mirrored and linear trilayer actuators to be constructed [ 36 ]. In either case, it is of paramount importance to understand the factors influencing the actuation mode, which in turn depends on the balance of the mobile species.…”
Section: Resultsmentioning
confidence: 99%